Effect of time interval and immunosuppressive treatment on durability of humoral immune response in rheumatoid arthritis patients following COVID-19 vaccination - Semiyan Muhamad Ali; Sanaa Gadbaan Hama (Zanco Journal of Medical Sciences)
Background and objective: The durability of humoral immune response for medium term period of COVID-19 vaccines in Rheumatoid arthritis patients and the role of immunosuppressive treatment have not been yet well investigated. Therefore, we aimed to evaluate the influence of time and immunosuppressive medications on the vaccine efficiency in rheumatoid arthritis patients compare to controls.